Validating the Italian version of the Adult Picky Eating Questionnaire. (October 2022) - Menghi, Leonardo; Endrizzi, Isabella; Cliceri, Danny; Zampini, Massimiliano; Giacalone, Davide; Gasperi, Flavia
Abstract: Interest in adult picky eating (PE), i.e., the unwillingness to eat familiar foods or try novel foods, has grown rapidly in the last decade as a result of its negative health consequences. Fairly poor data are available on the prevalence of PE in Italy, mostly due to the lack of a psychometrically sound tool to measure this construct. Thus, this contribution aimed at translating and validating the 20-item Adult Picky Eating Questionnaire (APEQ) for use in the Italian context. The APEQ was translated into Italian (IT-APEQ) following a standard forward–backward procedure and administered online to a large cohort of Italian adults (N = 1030, 69.9% women, 18–75 yo), who also completed a series of psychometric and dietary measures to test both the convergent and discriminant validity of the IT-APEQ. Confirmatory factor analysis supported the original four-factor structure of APEQ. The IT-APEQ showed invariance across genders, good internal consistency, and strong test–retest reliability (N = 599, 70.5% women, 18–75 yo). As expected, the IT-APEQ was positively associated with eating inflexibility, food neophobia, obsessive–compulsive disorder, and disgust propensity/sensitivity, whereas it was anticorrelated with indices of diet variety. Moreover, we documented for the first time a negative link between adult PE and adherence to the Mediterranean diet. Our results suggest that the IT-APEQ demonstrates sound psychometric properties. Hence, we advocate its future usage to shed light into other correlates of PE in the Italian context and bolster cross-cultural research on adult PE, which is key to developing targeted strategies aimed at improving diet diversity and quality.